The Discourse on the Relationship of Power between the State and the People in Indonesian Indie Band Song - Bahiroh Adilah (Jurnal Media dan Komunikasi, 2021)
This research focuses on analyzing the discourse of the power relation between the state and the people in Indonesia in the lyrics of the songs "Kami Belum Tentu" and "Padi Milik Rakyat" by Feast (group band). Intolerance became Indonesia main concern in 2018 especially Surabaya’s church bombing, which then elaborated on other issues related to the socio- economic and political phenomena in Indonesia. The two songs were chosen because they adequately describe the socio-economic and political conditions in Indonesia and related to various sectors of government.This study uses Normal Fairclough's critical discourse analysis method to read the discourse on power relations between the state and the people which is articulated in the lyrics of the two songs. The results of this study conclude that the discourse on power relations with the form of Governmentality is spread in various areas of government, including in the leadership of a democratic country, the education system in Indonesia, the law constitution of UU ITE, towards farm workers through Reforma Agraria, and also in the management of tax money in Indonesia. The people will always be in a repressive state power system and the state uses its political power to carry out hegemonic submissions that are detrimental to the people structurally and economically through the ISA (Ideological State Apparatus) and RSA (Repressive State Apparatus) which critized in Indonesian indie song lyric.